COVID-19 in Children and Adolescents with Endocrine Conditions - Kostopoulou, Eirini; Güemes, Maria; Shah, Pratik (Hormone and Metabolic Research, 2020)
The rapid spread of coronavirus disease (COVID-19) worldwide justifies global effort to combat the disease but also the need to review effective preventive strategies and medical management for potentially high-risk populations during the pandemic. Data regarding the COVID-19 manifestations in adults with underlying endocrine conditions, especially diabetes mellitus, are increasingly emerging. Albeit children and adolescents are considered to be affected in a milder manner, paucity of information regarding COVID-19 in children who suffer from endocrinopathies is available. The present review comprehensively collects recommendations issued by various health organizations and endocrine associations for the management of pediatric endocrine conditions during the pandemic. Adhering to the specific “sick day management rules” and undelayed seeking for medical advice are only needed in most of the cases, as the vast majority of children with endocrine disorders do not represent a high-risk population for contamination or severe presentation of COVID-19. Psychological implications in these children and adolescents are also considered.
Keywords: COVID-19; pediatrics; endocrine disease; diabetes mellitus; psychological aspects